Determination And Characteristic Oil Biomarker Of Illegal Crude Oil Production Using Mass Spectroscopy in Musi Banyuasin District - Edhi suryanto; Sri Haryati; Budhi Kuswan (Sriwijaya Journal of Environment, 2018)
AbstractSouth Sumatra is one of the largest petroleum producing provinces in Indonesia, especially in the region of Musi Banyuasin Petroleum resources other than legally cultivated by Pertamina as government representatives, but on the other hand the community also participate through Illegal Drilling activities. This study aims to determine the hydrocarbon content and characterization of petroleum produced illegally by communities in the Sangadesa, Babattoman and Keluang districts through the biomarker analysis of the distribution of n-Alkane C10-C34 (m/z: 57), pristane, phytane, sterane C27-C29 (m/z: 217,218,259) and specific biomarker using Gas Chromatography Mass Spectroscopy agilent GCMSD 6890/5973i with data analysis using MSD Chemstation F.01.01.2317 and Library Database NIST14. Petroleum samples taken from 10 illegal wells with a depth range of 80-250 meters and production period of 3 months until 3 years. Oil is produced through The illegal drilling is not the main oil source rock but the result of migration. Biomarkers Hydrocarbon analysis is one of the most widely used devices for exploration geochemistry, exploitation, production and forensic environment in the assessment and determination of sources of pollution related to petroleum material and derivatives very well. Keyword ; Crude oil,illegal drillling,biomarker,GC/MS,caracterization Abstrak (Indonesian)Sumatera Selatan salah satu propinsi penghasil minyak bumi terbesar di Indonesia, terutama di wilayah musi banyuasin. Sumber daya minyak bumi diusahakan secara legal oleh Pertamina, namun di sisi lain masyarakat turut mengelola  melalui kegiatan Pengeboran Ilegal yang menjadi permasalah sosial ekonomi yang rumit satu dekade ini. Penelitian ini bertujuan untuk mengetahui kandungan biomarker hidrokarbon dan karakteristik minyak bumi yang dihasilkan secara tidak sah oleh masyarakat di kecamatan Sangadesa, Babattoman dan Keluang melalui analisis biomarker n-Alkana C10-C34 (m/ z: 57), pristane/phytane,  sterane C27-C29 (m/z: 217,218,259) menggunakan Kromatografi Gas Mass Spektroskopi Agilent GCMSD 6890 / 5973i . Analisis data menggunakan MSD Chemstation F.01.01.2317 dan Library Database NIST14. Hasil penelitian meninjukan karakteristik distribusi biomarker hidrokarbon dalam sampel  sampel minyak dari lokasi Babattoman dan Keluang  biomarker n-Alkana C12 sampai C30 tidak ditemukan untuk menunjukkan bahwa minyak bumi memiliki biodegradasi moderat, sampel minyak dari Keban sedikit terdegradasi. Rasio Pr / Ph, Pr / nC17, dan Ph / nC18 menunjukkan sumber bahan organik sumber laut yang tersimpan dalam kondisi lingkungan anoksik pengendapan. Rasio diasterane / steranes untuk ekstrak yang dianalisis dan sampel minyak menunjukkan rasio rendah (0,09 - 0,23) menunjukkan batuan sumber penyimpan minyak berjenis batuan karbonat anoksik  Kata kunci ; Minyak bumi, pengeboran ilegal,biomarker, karakteristik